Chiral Phosphoric Acid Catalyzed Enantioselective Allylation of Aldehydes with Allyltrichlorosilane - 程柯 范甜甜 孙健 (Chinese journal of chemistry, 2011)
Easily accessible chiral phosphoric acid lb has been applied as efficient organocatalyst for the asymmetric al- lylation of aldehydes with allyltrichlorosilane. In the presence of 20 mol% of lb, the allylation of a broad range of aldehydes proceeded smoothly to give the corresponding homoallylic alcohol with up to 87% ee and 97% yield.